Noise characterization and exposure of indoor hockey officials - Johnesee, Katherine, author; Brazile, William, advisor; Sandfort, Delvin, committee member; Lipsey, Tiffany, committee member (Colorado State University. Libraries, 2015)
Noise in the workplace is a common occurrence. These sounds can have various characteristics that can affect each individual. Many people around the world subject themselves to loud noises at recreational activities including concerts, monster truck rallies, and sporting events. Some individuals also work these events as security employees, referees, and concession workers. Depending on the arena and the sport, games may take place one to four days a week at a particular venue. The National Institute for Occupational Safety and Health (NIOSH) identifies exposure to noise as one of the most common hazards associated with workplaces. According to the National USA Hockey League, there are over 20,000 registered officials (referee/linesman) regulating hockey in the United States. The identified hockey official population could be at risk of developing noise induced hearing loss (NIHL) because of the noise exposure at hockey games. For this study, personal noise dosimeters and a sound level meter were used to record noise exposures during hockey games for the 2014 season to ascertain if hockey referees were at increased risk of NIHL. A total of 30 personal noise samples and 20 area noise samples were collected. The study was completed in December 2014. The noise dosimetry results were compared to the Occupational Safety and Health Administration (OSHA) Permissible Exposure Limit (PEL), OSHA Action Level (AL), and American Conference for Governmental Industrial Hygienists (ACGIH) Threshold Limit Value (TLV). Noise dose was calculated for each official per game to determine if noise controls were warranted at this specific venue. No referees or linesmen were overexposed to noise when compared to the OSHA PEL. However, twenty-five referees and linesmen (89%) were overexposed to noise according to the ACGIH recommendations (85 dBA, 3 dB exchange rate), and two officials (7%) were exposed above the OSHA Action Level (85 dBA, 5 dB exchange rate). An average equivalent sound-pressure level (Leq) range of 79 dBA to 90 dBA was measured using a sound level meter at four locations in the arena over five games. In addition to area and personal monitoring, the number of whistle blows by the officials was counted during the first period of four games, and the average number of whistle blows per game for referees and linesmen was 60. According to previous researchers, whistle blows are one of the loudest and closest noise sources to referees. Some whistles reach sound levels as high as 116 dBA. Based on the results, it is recommended that this venue take preventative action in reducing noise exposure for hockey referees. Future research should continue sampling at sports arenas and focus on implementing control measures in hockey arenas.